Peningkatan Kompetensi Guru dalam Pengembangan Modul Pembelajaran STREAM Berbasis Nilai Keislaman melalui Pendekatan PAR di SMA Nurul Hayah - Indah Rizki Anugrah; Azmi Azhari; Idha Ayu Kusumaningrum; Nisa Aprilia Nisa (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This community service training was conducted by the chemistry education program team at Nurul Hayah Senior High School. The purpose of this activity was to provide training for teachers in developing learning modules that can be used as independent student learning materials or in the classroom. Interview results showed that teachers at this school still experience difficulties in developing modules, especially Islamic-based modules. In fact, Nurul Hayah Junior/Senior High School is an Islamic boarding school-based institution, so teaching materials integrated with Islamic values are essential. Meanwhile, available textbooks are still general in nature and not yet Islamic-based. Based on these interview results, community service activities needed to be carried out to improve teachers' abilities in developing Islamic-based learning modules. The module trained was a learning module based on the STREAM (Science, Technology, Religion, Engineering, Art, and Mathematics) approach. The method used in this service activity was Participatory Action Research (PAR), which includes four stages: to know, to plan, to act, and to reflect. The training participants were 30 teachers from Nurul Hayah Luragung and Pancalang Senior High Schools. Activities included lectures, discussions, demonstrations, presentations, and consultations conducted over eight weeks. Results showed 86.7% of participants successfully completed module development with good quality. This service activity has a positive impact on teachers, particularly in preparing Islamic-integrated teaching materials and introducing various assessment formats from two-tier to five-tier tests.